2007
DOI: 10.3748/wjg.v13.i15.2183
|View full text |Cite
|
Sign up to set email alerts
|

Safety and success of precut biliary sphincterotomy: Is it linked to experience or expertise

Abstract: AIM:To determine the rates of success and complications of precut biliary sphincterotomy (PBS) based on prior experience and to compare the complication rates between PBS and standard endoscopic sphincterotomy (ES). METHODS:A retrospective evaluation of prospectively collected non-randomized data at an academic tertiary referral center. The study included all patients in an eight-year period who underwent PBS and ES by a single endoscopist who had no formal training in PBS. The main outcome measures of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 21 publications
(7 reference statements)
3
32
0
Order By: Relevance
“…There was a significant increase in the cannulation rate from an initial 60 % in the first 40 patients, to 85 % in the last group. Robinson et al reported a similar pattern with an increase from 68 % to 76 % when comparing the first 50 patients with the subsequent group of 25 [11,17]. Therefore, our results demonstrate that some degree of improvement exists in the cannulation success rate with NKF as procedural experience increases, although this effect might be greater for some operators and smaller or minimal for others.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…There was a significant increase in the cannulation rate from an initial 60 % in the first 40 patients, to 85 % in the last group. Robinson et al reported a similar pattern with an increase from 68 % to 76 % when comparing the first 50 patients with the subsequent group of 25 [11,17]. Therefore, our results demonstrate that some degree of improvement exists in the cannulation success rate with NKF as procedural experience increases, although this effect might be greater for some operators and smaller or minimal for others.…”
supporting
confidence: 79%
“…Furthermore, as we cannot predict the innate skills of an endoscopist ab initium, a formal training period is recommended. The studies published often suggest 40 to 50 NKF as an adequate number of precuts for training, given that most endoscopists after this threshold report a needle-knife precut success above 70 % [5,11,14,16,17]. Although suggesting a minimum number of precuts for assessing proficiency in NKF is problematic, we propose 20 NKFs (and not 40 or 50) for the first moment of assessment.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In most cases, IT systems are standalone systems, without any ability of integration. In this way, different businesses processes are operating in silo which deters success of organization (Robison et al, 2007). One of the other factors which need to be taken into account in this respect is that the organizational actors have to ensure that they have the best systems put into place, which can enable the actors to develop and understand the issues of efficiency (Jun and Kim, 2010).…”
Section: Factors Impacting the Success Of Implementing New Business Smentioning
confidence: 99%
“…Another recommended way of use of IT is its ability to share important information and knowledge about customers choices (Robison et al, 2005). The way success is embedded in the use of IT system is that, newer ways of doing work will be initiated with the integration of IT system (Shutov, 2011) actors are able to implement the systems, and therefore the acceptance of new innovation is highly important for the organization (Chen and Chen, 2010).…”
Section: It Experiencementioning
confidence: 99%